Non-sterile gloves and dressing versus sterile gloves, dressings and drapes for suturing of traumatic wounds in the emergency department: a non-inferiority multicentre randomised controlled trial. Issue 9 (26th July 2022) - Zwaans, Juliette J M; Raven, Wouter; Rosendaal, Arthur V; Van Lieshout, Esther M M; Van Woerden, Geesje; Patka, Peter; Haagsma, Juanita A; Rood, Pleunie P M
Abstract : Background: Patients with traumatic wounds frequently present to the ED. Literature on whether to treat these wounds sterile or non-sterile is sparse. Non-sterile treatment has the advantage of saving resources and costs, and could be of value in health settings where sterile materials are not readily available. Our objective was to compare the rate of wound infection after suturing traumatic lacerations with non-sterile gloves and dressings versus sterile gloves, dressings and drapes in the ED. We hypothesised that non-sterile gloves and dressings would be non-inferior to sterile gloves, dressings and drapes. The non-inferiority margin was set at 2%. Methods: A multicentre single-blinded randomised controlled trial testing for non-inferiority of non-sterile gloves and dressings versus sterile gloves, dressings and drapes for suturing of traumatic wounds was performed in 3 EDs in The Netherlands. Adults with uncomplicated wounds were included from July 2012 to December 2016. At the time of treatment, patient and wound characteristics and management were documented. The outcome was wound infection, which was identified during follow-up in the treating ED at 5–14 days postprocedure. Results: From 2468 eligible patients, 1480 were randomised in a sterile (n=747) or non-sterile (n=733) protocol. Baseline characteristics were similar in both study arms. The observed wound infection rate in the non-sterile group was 5.7% (95% CI 4.0% to 7.5%) vs 6.8% (95% CI 5.1% to 8.8%) in the sterile group. The mean difference of the wound infection rate of the two groups was −1.1% (95% CI −3.7% to 1.5%). Conclusion: Although recruitment ceased prior to reaching our planned sample size, the findings suggest that there is unlikely to be a large difference between the non-sterile gloves and dressings for suturing of traumatic wounds and sterile gloves, dressings and drapes for suturing of traumatic wounds in the ED. Trial registration number: NL 34798.078.11, NTR3541.